Increased Lymphangiogenesis and Hemangiogenesis in Infant Cornea - Yuen, Don (Mary Ann Liebert, Inc., 2011)
BACKGROUND: Corneal lymphangiogenesis (LG) and hemangiogenesis (HG) accompany many diseases after inflammatory, infectious, traumatic or chemical insults. They also contribute to transplant rejection. It is known that corneal transplants in infants or children have a higher rejection rate than in adults. However, it has never been studied whether infant corneas differ from adult corneas in inflammatory LG, HG, or both, which is the focus of this study. METHODS AND RESULTS: Corneal inflammatory LG and HG were induced by a standard suture placement model in C57BL/6 mice of 3 weeks and 8 weeks of age, respectively. Corneal LG, HG, and macrophage infiltration were assessed by immunofluorescent microscopic studies using specific antibodies against CD31 (a panendothelial cell marker), LYVE-1 (a lymphatic marker), and F4/80 (a macrophage marker). Blood vessels were also examined by ophthalmic slit-lamp microscopic assays in vivo. Digital images were analyzed by NIH Image J software. It was found, for the first time, that infant corneas exhibited a higher level of LG, HG, and macrophage infiltration during inflammation. Infant lymphatic and blood vessels demonstrated greater density and invasion area but similar branching points. Additionally, infant lymphatic vessels were also of larger diameter. CONCLUSIONS: Infant and adult corneas differ greatly in their inflammatory responses of LG, HG, and macrophage infiltration. These novel findings will shed some light on our understanding of the LG and HG processes, as well as the development of new therapeutic protocols for corneal diseases, particularly, in infants or children, where an early restoration of sight is critically important in preventing amblyopia or permanent vision loss.